2012
DOI: 10.1021/ic2021319
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Diverse Copper(II) Complexes of Polyaza Ligands Containing 1,2,3-Triazoles: Site Selectivity and Magnetic Properties

Abstract: Copper(II) acetate mediated coupling reactions between 2,6-bis(azidomethyl)pyridine or 2-picolylazide and two terminal alkynes afford 1,2,3-triazolyl-containing ligands L(1)-L(6). These ligands contain various nitrogen-based Lewis basic sites including two different pyridyls, two nitrogen atoms on a 1,2,3-triazolyl ring, and the azido group. A rich structural diversity, which includes mononuclear and dinuclear complexes as well as one-dimensional polymers, was observed in the copper(II) complexes of L(1)-L(6).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 60 publications
4
46
0
Order By: Relevance
“…12,38,5055 We developed an experimental procedure based on Scheme 3 that allows for determining the affinity of N3 of 1,2,3-triazolyl group (see numbering in Scheme 3A) to zinc(II), which accounts for the difference in zinc(II) affinities of L14 and L15 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,38,5055 We developed an experimental procedure based on Scheme 3 that allows for determining the affinity of N3 of 1,2,3-triazolyl group (see numbering in Scheme 3A) to zinc(II), which accounts for the difference in zinc(II) affinities of L14 and L15 .…”
Section: Resultsmentioning
confidence: 99%
“…11,12 The renaissance of 1,2,3-triazole chemistry is primarily due to the discovery by Fokin, Sharpless, 13 and Meldal 14 of regiospecific synthesis of 1,4- disubstituted-1,2,3-triazoles via the copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC). It was later shown that 1,5-disubstituted-1,2,3-triazoles can be prepared also regioselectively using Ru- or base-catalyzed approaches (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…8,79,80 These bidentate click ligands form rhenium(I) complexes with a 1 : 1 metal : ligand ratio. The complexes of these ligands have wide applications in electronic 81,82 and luminescent 29,[83][84][85][86][87][88][89] materials, catalysts, [90][91][92] and in metallo-pharmaceuticals.…”
Section: 23-triazole-containing Chelators: Click Synthetic Visionmentioning
confidence: 99%
“…We [39][40][41][42][43][44] and others [45][46][47][48][49][50][51][52][53][54][55] have explored the use of 1,4-disubstituted 1,2,3-triazole containing ''click'' ligands in the development of functionalized metallosupramolecular architectures and have shown that metallomacrocycles, cages and helicates can be readily generated. As part of that work we developed a small family of bis-2-(1-R-1H-1,2,3-triazol-4-yl)pyridine ligands 1 [56] (Scheme 1) and showed that they would assemble into [Fe 2 L 3 ] 4+ metallosupramolecular helicates [57] when treated with Fe(II) ions.…”
Section: Introductionmentioning
confidence: 99%